Urban planning – architectural report on thermal stress in the city of Madrid - Torrego Gómez, Daniel (Zenodo, 2021)
This report serves the EmCliC research project ( Embodying Climate Change ) as an analysis on the influence of architecture and urban planning on the experiences of thermal stress in the city of Madrid. It reviews the existing bibliography on the role of the urban fabric on the Urban Heat Island effect, with special focus on the different building typologies, construction solutions, materials, urban blue infrastructure or presence of green areas. This work, in addition, aims to offer a broad vision that is not restricted to the technical, but that values social, political and cultural issues as relevant elements when analyzing the relationship of the architecture of the city with overheating and, consequently, with the Climate Change. Thermal performance of the city, is integrated in this study in a broader ecosystem of interests, policies, regulations and projects, as well as in its “built” history. With that goal, the analysis focuses on the situated and embodied experiences of thermal stress, from the point of view of architecture and urban planning. The object of study, therefore, will be the Urban Heat Island (UHI). The methodology will be to reinterpret the UHI of Madrid, basing on the given cartographies, but attending to more specific and embodied conditions. Therefore, the UHI will not be only be analyzed as a shape that covers the city, but as something more concrete, that is dependent on specific and situated assemblages of heterogeneous phenomena such as urban density, presence -or absence- of air currents, thermal buffers, radiant surfaces, the actions of neighbors, or bioclimatic ordinances. The Embodying Climate Change project is funded by Iceland, Liechtenstein and Norway through the EEA Grants.